Clustering and routing in mobile ad hoc networks (MANETs) - Yu, Yang (2010)
Mobile Ad Hoc Networks (MANETs), without any fixed infrastructures, allow wireless communication terminals to build communication networks anytime and anywhere. Hence, MANETs bear great application potential and become a hot research topic in recent years. However, MANETs still face a lot of challenging problems, which may greatly affect their performance and application in practical situations. In this Thesis, we mainly focus on two challenging problems of MANETs: scalability and energy limitation, and come up with some clustering and routing protocols to solve the addressed problems. A MANET with flat structure encounters scalability problem with increased network size, in particular in face of node mobility. Cluster structure, as a typical hierarchy architecture, is essential for solving the scalability problem of MANETs and achieving performance guarantee in a MANET with moderate to large size. In this Thesis, we first give a comprehensive survey on some typical clustering schemes proposed in MANET research. We give the fundamental knowledge for MANET clustering, show the pros and cons of cluster based MANETs, categorize those proposed clustering schemes based on their objectives, and discuss their mechanisms, cost and feasible applications in detail. Secondly, we propose a clustering scheme, named efficient clustering scheme (ECS), for large and dense MANETs. With the introduction of a new cluster-related status, named clusterguest (CG), and a cluster deletion mechanism, ECS can effectively eliminate small and unnecessary clusters and hence effectively reduce the cluster overlapping in a MANET with moderate to high node density, which is helpful in simplifying the network structure.